“Equipamiento Complementario Residencia Estudiantil Universitaria para la Universidad Estatal de Bolivar - Guaranda” - Cuenca García, Carlos Israel (2018)
Nowadays, Higher Educations Institutions are facing process of change in our country, this change demands that they provide complementary quality services, many young students have left their place of origin, looking for a degree, therefore, it is necessary to offer places of residence for students form province, where they can stay the time that lasts their academic preparation. The new University Student Residence in the city of Guaranda, tries to satisfy the housing needs of university students, providing environments of quality and comfort, where there is not only the learning exist through teachers, but also of the experiences acquired in this less formal place. The subject of the thesis that has been presented has the purpose of proposing a design for a University Student Residence, in the search of functionality providing an academic improvement to the students and contribution in terms of accommodation, food and security, which At present, this type of equipment is not available, therefore, proposing this project will be a great contribution offered by the university.